Menjamin Perlindungan Hukum Bagi Pelapor Indonesia dalam Kasus Korupsi - Raj Ravicky Fardenias; Frans Simangunsong (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
The presence of a Whistleblower will aid law enforcement and make it simpler to unearth a criminal case of corruption, highlighting the critical role of the reporter in law enforcement. Consequently, whistleblowers should be granted legal protection by the state to ensure that their rights are safeguarded. Additionally, the state should recognize and reward those who blow the whistle on wrongdoing in order to show its gratitude for their assistance to law enforcement and their role in safeguarding the nation. So, a number of issues will be addressed by this study. Whistleblowers in Indonesia are legally protected from criminal prosecution in instances of corruption. (2) Procedures established by legislation within the context of criminal law to protect those who blow the whistle on corrupt officials. Normative methodologies derived from previously published books and papers are used in this study.